Efficient plasmonic coupling between Er3+:(Ag/Au) in tellurite glasses - Rivera, V. A. G.; Ledemi, Y.; Osorio, S. P. A.; Manzani, D. [UNESP]; Messaddeq, Younes [UNESP]; Nunes, L. A. O.; Marega, E. (Elsevier B.V., 2012)
We report a systematic study of the localized surface plasmon resonance effects on the photoluminescence of Er3+-doped tellurite glasses containing Silver or Gold nanoparticles. The Silver and Gold nanoparticles are obtained by means of reduction of Ag ions (Ag+ -> Ag-0) or Au ions (Au3+ -> Au-0) during the melting process followed by the formation of nanoparticles by heat treatment of the glasses. Absorption and photoluminescence spectra reveal particular features of the interaction between the metallic nanoparticles and Er3+ ions. The photoluminescence enhancement observed is due to dipole coupling of Silver nanoparticles with the I-4(13/2) -> I-4(15/2) Er3+ transition and Gold nanoparticles with the H-2(11/2)-> I-4(13/2) (805 nm) and S-4(3/2) -> I-4(13/2) (840 nm) Er3+ transitions. Such process is achieved via an efficient coupling yielding an energy transfer from the nanoparticles to the Er3+ ions, which is confirmed from the theoretical spectra calculated through the decay rate. Crown Copyright (C) 2011 Published by Elsevier B.V. All rights reserved.
Keywords: Tellurite glass; Metallic nanoparticles; Plasmonic; Localized surface plasmon resonance